Resonating Moment: Who can sail without the wind - Artful Dementia Research Lab (Zenodo, 2022)
The piece was co-created in 2020 during a situated art intervention at a residential care home in Northern Norway. Itdocumentsa resonating moment that was created andanalyzed within Artful Dementia Research Lab at UiT The Arctic University of Norway. Ref: Dalby, K., Mittner, L., & Gürgens, R. (forthcoming). Consent as an aesthetic process. Nordic Journal of Arts, Culture and Health .